Pengaruh Larutan Aktivator, Waktu Kontak dan pH Larutan dalam Pembuatan Biosorben Kulit Buah Aren (Arenga Pinnata) untuk Adsorpsi Timbal dalam Limbah Cair Tekstil - Rubiana Sihotang (Ridwan Institute, 2021)
Textile wastewater which generally has a high pollution load can be overcome by the low-cost natural biosorbent. The purpose of this study was to obtain the best activator solvent, contact time and pH of biosorbent from Arenga pinnata shell for removal of lead in textile wastewater and to determine the adsorption isotherm model. Arenga pinnata shell have been used for the removal of Pb (II) ions from textile wastewater in batch experiments with factorial Completely Randomized Design (CRD) method. The results showed that the most effective activator solvent was NaOH, while the optimum contact time was 120 minutes and the optimum pH was 4. The highest Pb (II) uptake is 99,91% with adsoption capacity of 1,5879 mg/g. The lowest end levels of Lead in textile wastewater was 0,06 ppm which these results has met the liquid waste quality standard for industrial activities (1 ppm). Sorption data conformed better in Langmuir isoterm model than freundlich with adsoption capacity of 117,65 mg/g. The results showed that biosorbent of Arenga pinnata shell is effective in removing lead from the textile wastewater.